Role of basal hormones on sweat rate and sweat Na+ loss in elite women soccer players - Castro-Sepulveda, M.; Cancino, J.; Jannas-Vela, S.; Jesam, F.; Lobos, C.; Del Coso, J.; Zbinden-Foncea, H. (International Journal of Sports Medicine, 2020)
We aimed to determine whether basal concentrations of testosterone, cortisol or the ratio testosterone/cortisol were related to sweat Na+ loss, sweat Na+ concentration ([Na+]) and sweat rate during exercise. Twenty-two female elite soccer players participated in the study. Testosterone and cortisol were measured in blood samples before exercise. Sweat samples were collected during a training session (~20°C, ~30% RH, and ~0.55 m/s of wind speed) to measure sweat [Na+]. Sweat rate was determined by considering the difference between post-and pre-body weight, along with the amount of liquid consumed. During exercise, sweat Na+ loss (0.33[0.19] g/h) and sweat rate (0.49[0.20] L/h) were related to basal testosterone concentration (1.4[0.4] pg/mL) (r=0.54; r=0.55, respectively; p<0.05), but not with basal cortisol concentration (119.2[24.2] ng/mL) nor testosterone/cortisol ratio (0.012[0.003]) (p>0.05). However, when Na+ loss was adjusted to sweat rate, no association was found between Na+ loss and testosterone (p>0.05). In addition, no differences were found between players with high vs. low Na+ loss adjusted to sweat loss in menstrual phase or intensity during exercise (p>0.05). In conclusion, these results suggest that in these specific environmental conditions, basal levels of testosterone might increase sweat rate and therefore, the amount of Na+ lost during exercise in elite women soccer players.